The Study and Analysis of the Exemplary Mother Archetype in Simin Behbahani’s Poems - ghodrattollah alirezaei; Gholamreza Salemian; fateme kolahchian (زن در فرهنگ و هنر)
In his analytical psychology, the Swiss psychiatrist Jung has proposed numerous archetypes that can serve as valuable criteria for evaluating, reviewing, and analyzing the literary works of psychological critique. The “exemplary mother” archetype is a mental and universal image of human personality and individuality that is manifested in both positive and negative forms. It is one of the most essential and vital archetypes. Simin Behbahani is a contemporary Persian poet whose poems are a reflection of her motherly exemplary deeds. The current study, which employs an analytical-descriptive method, aims to identify the positive and negative manifestations of the mother in Simin Behbahani’s poetic concepts and structures, as well as to uncover the archeological exemplary manifestations of the mother in the context of mythological-psychological critique. The findings indicate that the exemplary mother’s positive and negative manifestations are represented by 60% and 40%, respectively. She cites Simin Behbahani’s poetry as an example of the most prevalent manifestations of the spring season in the positive form, which include frequency, plant identification, congenital, reproduction, enthusiasm, enthusiasm, The sun and the homeland. The negative aspect is characterized by the maximum frequency of negative seasons(summer, autumn and winter), death thinking, night, swamp, sterile ground and City